The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/398_2019_35
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Prognosis of Malaria Vector Control Pesticide Ecotoxicology and Xenopus sp.

Abstract: Whilst frogs are generally considered as good indicators of environmental change, they are not widely utilised as indicators in ecological studies. With much of current research relying on model organisms as proxies for other animals or even humans, toxicology data on these model organisms is important for higher tier risk assessment studies and ecological modelling. The issue at hand is that for some topics, even when looking at model organisms, this empirical data does not seem to be as common as expected wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
6
0
3
Order By: Relevance
“…The validation results of the extraction and analysis methods for DTM used in this study indicated that the method was effective for the extraction and analysis of DTM. No published literature is available on the accumulation of DTM in Xenopus tissue (see Wolmarans et al 2020). Studies on fish such as Szegletes et al (1995) also failed to measure DTM residues in tissue samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation results of the extraction and analysis methods for DTM used in this study indicated that the method was effective for the extraction and analysis of DTM. No published literature is available on the accumulation of DTM in Xenopus tissue (see Wolmarans et al 2020). Studies on fish such as Szegletes et al (1995) also failed to measure DTM residues in tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…The two pesticides tested, DDT and DTM, were selected in this study as representatives of IRS pesticides. The scope of this study and ethical limitations on the use of vertebrate animals did not allow for extensive LC50 testing on adult frogs, and no literature containing LC50 data on adult X. laevis was found in a recent review (see Wolmarans et al 2020). Therefore, the LC50FETAX values (DDT= 35.7 mg/L and DTM = 0.19 mg/L, Channing 1998;Saka 2004) based on toxicity to larval X. laevis were used as a starting point for lethality, even though sensitivity between adult and developmental stages of animals can differ.…”
Section: Pesticide Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, o potencial de acumulação de outros pesticidas em sapos é desconhecido. Detectou-se que malationa e alguns piretroides apresentaram toxicidade para este modelo 15 . Um estudo considerou metopreno e Bti como inseticidas de baixo risco para organismos não alvo com base nas concentrações detectadas no ambiente 63 .…”
Section: Estudos Ecotoxicológicos Dos Ingredientes Ativos Presentes E...unclassified
“…Organoclorados, como o dicloro-difenil-tricloroetano (DDT), apesar de terem sido banidos em muitos países, são os pesticidas encontrados em maior concentração no solo e na água em virtude de sua lenta biodegradabilidade 13,14 . Outro prejuízo ambiental referente ao uso de inseticidas está relacionado aos efeitos em organismos não alvo, como animais aquáticos, répteis, anfíbios, plantas e polinizadores 15 . Não só os inseticidas ambientais, mas aqueles aplicados na pele apresentam risco ao meio ambiente 16 .…”
Section: Introductionunclassified